English learning anxiety of Chinese rural junior high school students under the online class mode - Yu, Qiangfu; Xu, Dazhou; Huang, Rui (Frontiers in Psychology, 2023)
The Covid-19 pandemic has brought tremendous changes to the field of education, transferring traditional offline teaching to online teaching on a large scale globally. Junior high school students, as a special group, may experience foreign language learning anxiety different from anxiety experienced by college students in the process of online English learning. This research aims at investigating the level of, sources and strategies for English learning anxiety of Chinese rural junior high school students under online class mode. A total of 120 students from Dongshan Junior High School in Haikou participated in this study and asked to fill in the questionnaires, and 12 of them were randomly chosen to be interviewed. IBM SPSS Statistics 26 was used to analyze the data. This research found that Chinese rural junior high school students generally had a moderate level of English learning anxiety, and there is statistically no significant relation between the gender difference and anxiety in online foreign language classes. It was also found that factors influencing English learning anxiety of Chinese rural junior high school students included the students themselves, their home environments, the teacher and the school, and the social environment. Lastly, the research found five strategies to relieve foreign language learning anxiety, including recognizing the existence of anxiety correctly, communicating the anxiety honestly with others, improving the psychological quality, being positive about life’ s setbacks, and setting up some realistic goals in English learning.